Case report: Endovascular embolization of a cerebral pseudoaneurysm caused by SARS-CoV2 infection - García-Carmona, Juan Antonio; von Quednow, Enzo; Hernández-Fernández, Francisco; Molina-Nuevo, Juan David; García-García, Jorge; Palao, María; Segura, Tomás (Frontiers in Neurology, 2022)
Background Severe COVID-19 has been shown to produce convulsions, encephalitis, Guillain-Barré syndrome, or cerebrovascular disease. However, only 4 case reports described subarachnoid or brain hemorrhage caused by ruptured cerebral aneurysms or pseudoaneurysms in patients with COVID-19. Cerebral pseudoaneurysms represent <1% of all intracranial aneurysms and have been related to radiation therapy, vasculitis, rupture of true saccular aneurysms, arteriovenous malformations, and infections by bacteria and viruses, such as Epstein-Bar and Herpes virus. Case presentation A 28-year-old Caucasian woman, with no medical history of interest and completely vaccinated against SARS-CoV-2, was admitted to Neurology due to progressive tetraparesis with areflexia, a cough, and a fever of 38°C. SARS-CoV2 PCR was positive while lumbar puncture, blood tests, and electromyogram showed criteria for Guillain-Barré syndrome. Despite the treatment, the patient developed dyspnea and tetraplegia requiring invasive mechanical ventilation. There was motor neurological improvement but a decreased level of consciousness was observed on day 13. A brain CT scan demonstrated an acute haematoma and cerebral arteriography showed a 4-mm pseudoaneurysm located in a branch of the left middle cerebral artery. Given the high risk of rebleeding, endovascular treatment was decided upon. Therefore, complete embolization of the pseudoaneurysm was carried out by using the synthetic glue N-butyl-cyanocrylate. Two days later, the patient was clinically and neurologically recovered and was discharged. Lastly, a new angiography showed no evidence of the pseudoaneurysm 3-weeks later. Conclusions We report, for the first time, a patient suffering a severe immune reaction caused by SARS-CoV2 infection and developing a cerebral pseudoaneurysm treated with endovascular embolization without complications.